Institutional Violence against People with Disability: Recent Legal and Political Developments - Cadwallader, Jessica Robyn; Spivakovsky, Claire; Steele, Linda; Wadiwel, Dinesh (Current issues in criminal justice, 2018)
International and Australian domestic evidence suggest that the prevalence of violence against people with disability is substantially higher than for the rest of the community. Much of the violence experienced by people with disability in Australia occurs within the purview of a variety of institutions, including group homes, large residential institutions, Australian Disability Enterprises (that is, disability employment facilities), schools, psychiatric facilities, hospitals and correctional facilities. This comment discusses recent domestic and international legal and political attempts to grapple with the issue of institutional violence against people with disability, focusing in particular on a series of Senate Committee inquiries into abuse and violence, regulation related to the National Disability Insurance Scheme, the coming into force of the Convention on the Rights of Persons with Disabilities, Australia's anticipated ratification of the Optional Protocol to the Convention Against Torture and recent calls by Disability People's Organisations and academics for a Royal Commission into violence against people with disability.